Pengaruh Minuman Jahe Terhadap Tingkat Nyeri Menstruasi pada Remaja Putri di Kelurahan Candirejo: The Effect of Ginger Drinks on Menstrual Pain Levels in Adolescent Girls in Candirejo Village - Rini Susanti; Sari, Kartika; Jatmiko Susilo (Universitas Ngudi waluyo, 2023)
Dysmenorrhea or pain during the menstrual cycle with the prevalence of dysmenorrhea varying between 16% and 91% in women of childbearing age, with severe pain in 2%-29% of women which has a major impact on the quality of life and work productivity.This study aims to analyze the effect of drinking ginger on the sensation of menstrual pain (dysmenorrhea) in young women in Candirejo, Ungaran. Quasi-experimental research using one group pre-post test design. A total of 13 subjects (consecutive sampling), were young women aged 19 - 24 years, unmarried and experiencing dysmenorrhea. Subjects drank 2 packs of ginger a day starting from two days before until the third day of menstruation. Data was taken using the Numeric Rating Scale, Verbal Multidimensional Scoring System, and Brief Pain Inventory. Subjects were 22.15 ± 1.72 years old, menarche age 12.69 ± 1.18 years. The average pain sensation before was 3.38 ± 0.96 and after drinking ginger was 1.15 ± 1.07 on the pain scale. Giving ginger to drink can significantly reduce the sensation of menstrual pain,(p<0.001). Giving ginger drinks has the effect of reducing the sensation of menstrual pain in young women in Candirejo, Ungaran. Teenagers are expected to use ginger drinks to treat pain during menstruation which is cheap and safe. Abstrak Dismenore atau nyeri selama siklus menstruasi dengan prevalensi dismenore bervariasi antara 16% dan 91% pada wanita usia subur, dengan nyeri hebat pada 2%-29% wanita yang berdampak besar pada kualitas hidup, dan produktivitas kerja perempuan. Penelitian ini bertujuan untuk menganalisis pengaruh minum jahe terhadap sensasi nyeri mestruasi (dismenore) pada remaja putri di Keluarahan Candirejo, Ungaran. Penelitian kuasi eksperimental menggunakan one group pre-post test design. Sebanyak 13 subyek (consecutive sampling) remaja putri usia 19 – 24 tahun, belum menikah dan mengalami dismenore Subyek meminum jaheR sebanyak 2 bungkus sehari dimulai dari dua hari sebelum hingga hari ketiga menstruasi. Data diambil menggunakan Numeric Rating Scale, Verbal Multidimensional Scoring System, dan Brief Pain Inventory. Subyek berumur 22,15 ±1,72 tahun, usia menarche 12,69 ± 1,18 tahun. Rata-rata sensasi nyeri sebelum 3,38 ± 0,96 dan sesudah minum jahe 1,15 ± 1,07 skala nyeri. Pemberian minum jahe dapat menurunkan sensasi nyeri menstruasi remaja putri secara bermakna (p< 0,001). Pemberian minuman jahe berpengaruh menurunkan sensasi nyeri menstruasi pada remaja putri di Kelurahan Candirejo Ungaran. Remaja diharapkan menggunakan minuman jahe untuk mengatasi nyeri saat menstruasi yang murah dan aman.